2019
DOI: 10.1021/acssuschemeng.9b00807
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous-Phase Glycerol Catalysis and Kinetics with in Situ Hydrogen Formation

Abstract: Hydrodeoxygenation (HDO) is a widely used technology to convert biomass-based feedstock into value-added fuels and chemical products that usually require high-pressure hydrogen (H2) to remove excess oxygen in the biomass feedstock. To make this process safer and more sustainable, we investigated glycerol conversion under an inert atmosphere in aqueous media using multimetallic catalysts (comprised of Ru, Re, and Pt) supported on activated carbon. Here we report a trimetallic Ru-Re-Pt catalyst that converts gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…According to the product distribution (Figure 2) and literature reference, 24,43,44 we proposed reaction pathways (Figure 3 Based on the discussion mentioned above, it can be seen that the presence of bimetallic Pd−Pt nanoparticles is able to catalyze tandem H 2 generation and hydrogenolysis of xylitol; thus, the formation of glycols can be well achieved even in the absence of externally added H 2 .…”
Section: Resultsmentioning
confidence: 92%
“…According to the product distribution (Figure 2) and literature reference, 24,43,44 we proposed reaction pathways (Figure 3 Based on the discussion mentioned above, it can be seen that the presence of bimetallic Pd−Pt nanoparticles is able to catalyze tandem H 2 generation and hydrogenolysis of xylitol; thus, the formation of glycols can be well achieved even in the absence of externally added H 2 .…”
Section: Resultsmentioning
confidence: 92%
“…Type A : In‐situ hydrogenolysis without using external H‐donors . Extensive studies have been reported in recent years on glycerol hydrogenolysis to 1,2‐PDO using H 2 generated in‐situ [7–8,30a,b] . Very limited efforts have been devoted to this area, because rational design of bifunctional materials to transform glycerol in simultaneous C−O and C−H cleavage is very challenging [5d,9] .…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] It is worth noting that highly efficient and selective hydrogenolysis of glycerol to 1,2-PDO has been achieved on various catalytic systems. [7,[15][16][17][18][19][20] Although the dehydration of 1,2-PDO to propanal (PA) has also been studied using various types of heterogeneous catalysts, the catalytic activity and selectivity to PA still remains a huge challenge. [21][22][23][24][25][26] The PA with a reactive formyl group is an important potential intermediate material to produce high value-added chemicals such as rubbers, plastics, paints, and pesticides, which are commercially produced from fossil resources now.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, one of the most promising approaches is the catalytic hydrogenolysis of glycerol into propanediols, such as 1,3‐propanediol (1,3‐PDO) and 1,2‐propanediol (1,2‐PDO) . It is worth noting that highly efficient and selective hydrogenolysis of glycerol to 1,2‐PDO has been achieved on various catalytic systems …”
Section: Introductionmentioning
confidence: 99%